Application of bioluminescence ATP measurement for evaluation of fungal viability of foxing spots on old documents. (14th June 2012) - Rakotonirainy, Malalanirina Sylvia; Dubar, Pauline
ABSTRACT: An adenosine triphosphate (ATP) bioluminescence‐based protocol was tested to assess the viability of fungal species in old documents damaged by foxing. Foxing appears as scattered yellow brownish‐red stains, damaging the aesthetics of documents and their long‐term readability. In the field of cultural heritage conservation, the debate over the mechanism of foxing is ongoing. Previous studies found evidence of mold‐like structures in some coloured areas; however, many species have not yet been identified and their role in the phenomenon is not understood. To better understand their involvement in this type of paper decay, we focused our attention first on their viability. We demonstrated the reliability and sensitivity of the ATP bioluminescence assay compared with conventional methods based on cultivation, which has rarely given rise to in vitro growth from foxed papers. From nine books dating back from the 19th and 20th centuries, the mean ATP amount of foxed spots ranged from 0.29 to 3.63 ng/cm 2, suggesting the presence of strains inside the brownish spots and providing evidence of their viability. Outside the spots, ATP content was considered negligible, with a mean ATP amount of 0 to 0.03 ng/cm 2 . ATP assay appears to be a useful and robust method for the detection and quantification of viable elements in foxing spots. Copyright © 2012 John Wiley & Sons, Ltd.